Processo de vulnerabilização em saúde sexual de lésbicas : vivência em um serviço especializado em IST/HIV/Aids de Cuiabá - Reis, Kamylla Cavalcante Taques dos (2022)
This dissertation focuses on the discussion of the (non)production of health and public sexual health policies for lesbian, exploring the process of vulnerability in health to understand the scenario of social invisibility that results in the lack of perception of their demands with health services. Through ethnographic research in a Specialized Care Service in STI/HIV/AIDS and Viral Hepatitis in Cuiabá/MT, we sought to investigate how health is (not) produced for these population, in a space marked by power and disputes. The notion of social vulnerability that permeates the construction of public health policies aimed at AIDS, in which vulnerability is understood, in its complex conceptual field, by multiple conditions of different natures (economic, cultural or social), which is not inherent, but determined by conditions and circumstances, provided the empirical basis for data analysis. The daily life of health professionals is observed, permeated by the preventive model, which directly or indirectly influences the implementation of public policies. Furthermore, it considers the hierarchies that constitute the convergence between the axes of gender, race and class in the moralization of the AIDS epidemic and its effects on the construction of the identity of People Living with HIV (PLHIV) and on the erasure of sexual and reproductive rights of lesbian, resulting in the process of vulnerability in health.